Edukasi Ketahanan Pangan Rumah Tangga Melalui Optimalisasi Sumber Daya Lokal: Studi Kasus Desa Sidera, Kabupaten Sigi, Sulawesi Tengah - Laendatu Paembonan; Farida Millias Tuty; MUBARAK, MUHAMMAD SYAHRUL; Nurfadilah Sindika Sari; Andi Herman Jaya (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
Food security challenges in Sidera Village include limited access to natural resources, low levels of education, and minimal public awareness of home-yard farming practices. This community service activity aims to implement a household empowerment-based intervention model through the use of yards as a source of healthy and sustainable food. The main target is housewives in Sidera Village, Kecamatan Sigi Kota, Kabupaten Sigi, as the primary managers of family food consumption. The implementation method is as follows: first, preparation and socialization; second, training and implementation of home-yard utilization; third, education on nutrition and consumption patterns; and finally, mentoring. The results of the activity showed that in the first phase, the community had not yet utilized their yards productively. The second phase succeeded in encouraging participants to plant at least two types of food crops in their yards. The third phase increased participants understanding of vegetable processing and consumption cost efficiency. In the final phase, challenges were encountered in the form of pest attacks, unpredictable weather, and limited water supplies. This activity demonstrated that household empowerment-based interventions can increase food availability, reduce expenses, and strengthen community participation in the sustainable management of local food sources.